Collaboration scope and product innovation in B2B markets: are there too many cooks or is it the customer who spoils the broth?. (23rd March 2022) - Mooi, Erik; Osinga, Ernst Christiaan; Santos, Carlos Daniel
Abstract : Purpose: Product innovations are often the result of combinations of internal and external knowledge. A significant amount of open innovation literature has argued that working with external partners can be beneficial, in particular, when this is complemented by internal R&D, yet a wholesale shift to open innovation has not occurred. The purpose of this study is to demonstrate two new limits of openness, grounded in attention-based theory, that help explain why such a shift has not occurred. This study argues that specific combinations of identities a firm collaborates with, that is, whether a partner is classified as a customer, supplier, competitor or university and/or technological center, predictably increase and decrease product innovation. Design/methodology/approach: This study demonstrates these findings using econometric techniques on a large-scale panel data set, comprising 14, 682 observations. Findings: The authors observe positive effects of customer collaboration, partner scope (collaboration with other outside identities) and internal R&D when considered separately. Critically, they observe two important situations where these positive effects are reduced. First, they argue and observe that when customers are added to the mix of identities, diminished returns on product innovation result. Second, they argue and observe that technological customer collaboration reduces the benefits from an internal R&D department (more than collaboration with other identities). The findings of this study are robust in that singling out another partner identity does not reveal such patterns. Research limitations/implications: The findings stress the importance of considering the identity of collaborating parties in studying the impact of openness on innovation success. This study conceptually and empirically rejects the – implicitly held – assumption in the literature that different partners provide similar benefits and are interchangeable. Practical implications: This study proposes new limits to the "open innovation" literature. As identities are easy to observe by managers and are shown to impact product innovation, this study argues they are highly relevant to managerial decision-making. This study also observes, through counterfactual analysis, that attention limits are critical, as a theoretical setting of no attention limits would significantly lift product innovations. Originality/value: This study shows important limitations to the open innovation literature by showing that customer collaboration leads to declining rates of product innovation when combined with greater collaboration scope or the internal R&D department. This study adds the novel insight that customer collaboration weakens the positive effect of collaboration scope and internal R&D on product innovations.